Effects of chilling on the photosynthetic performance of the CAM orchid Phalaenopsis - Daems, Stijn; Ceusters, Nathalie; Valcke, Roland; Ceusters, Johan (Frontiers in Plant Science, 2022)
Crassulacean acid metabolism (CAM) is one of the three main metabolic adaptations for CO2 fixation found in plants. A striking feature for these plants is nocturnal carbon fixation and diurnal decarboxylation of malic acid to feed Rubisco with CO2 behind closed stomata, thereby saving considerable amounts of water. Compared to the effects of high temperatures, drought, and light, much less information is available about the effects of chilling temperatures on CAM plants. In addition a lot of CAM ornamentals are grown in heated greenhouses, urging for a deeper understanding about the physiological responses to chilling in order to increase sustainability in the horticultural sector. The present study focuses on the impact of chilling temperatures (10 °C) for 3 weeks on the photosynthetic performance of the obligate CAM orchid Phalaenopsis ‘Edessa’. Detailed assessments of the light reactions were performed by analyzing chlorophyll a fluorescence induction (OJIP) parameters and the carbon fixation reactions by measuring diel leaf gas exchange and diel metabolite patterns. Results showed that chilling already affected the light reactions after 24h. Whilst the potential efficiency of photosystem II (PSII) (Fv/Fm) was not yet influenced, a massive decrease in the performance index (PIabs) was noticed. This decrease did not depict an overall downregulation of PSII related energy fluxes since energy absorption and dissipation remained uninfluenced whilst the trapped energy and reduction flux were upregulated. This might point to the presence of short-term adaptation mechanisms to chilling stress. However, in the longer term the electron transport chain from PSII to PSI was affected, impacting both ATP and NADPH provision. To avoid over-excitation and photodamage plants showed a massive increase in thermal dissipation. These considerations are also in line with carbon fixation data showing initial signs of cold adaptation by achieving comparable Rubisco activity compared to unstressed plants but increasing daytime stomatal opening in order to capture a higher proportion of CO2 during daytime. However, in accordance with the light reactions data, Rubisco activity declined and stomatal conductance and CO2 uptake diminished to near zero levels after three weeks, indicating that plants were not successful in cold acclimation on the longer term.